PENGARUH KUALITAS PRODUK, VARIASI PRODUK DAN WoM (WORD oF MOUTH) TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA DISTRO POLKA SPACE - Putra, Yogi Pramudya; Maskuri Sutomo; Umar Syarifuddin; Farid (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
This study aims to identify and analyze the extent to which product quality, product variety, and Word of Mouth influence consumer purchasing decisions, in order to help Distro Polka Space in improving its marketing strategy. This study uses a quantitative approach, the data collection technique in this study used a questionnaire distributed to 90 Distro Polka Space consumers. The results of this study indicate that product quality, product variety, and word of mouth simultaneously and partially have a significant effect on purchasing decisions of Polka Space consumers. Consumers tend to make purchases when the product has good quality, a variety of choices that match trends, and get positive recommendations from others. Therefore, Distro Polka Space is advised to continue to improve the quality and variety of its products and encourage the spread of positive consumer experiences through social media to strengthen purchasing decisions.